GAMBARAN ABNORMALITAS ELEKTROKARDIOGRAM PADA PASIEN GAGAL JANTUNG DEWASA DI RSUD DR. M. HAULUSSY KOTA AMBON TAHUN 2019-2021 - Abdillah F.A Hasanusi; Ir wan; Nathalie E. Kailola (PAMERI, 2022)
Heart failure is one of the cardiovascular spectrum and a major cause of morbidity and mortality worldwide. Electrocardiogram (ECG) is a supporting examination in diagnosing heart failure. This study aims to determine the description of ECG abnormalities in adult heart failure patients in RSUD DR. M. Haulussy Ambon City in 2019-2021. This research is a descriptive study with a cross sectional design and 126 samples were selected using a simple random sampling technique. The results showed that the most ECG abnormalities were T inverted 37.3%, pathological Q 31%, prolonged QT interval 25.4%, LVH 23.8%, atrial fibrillation 19.8%, poor R wave 13.5%. , ST depression 12.7%, AV block grade 1 10.3%, ventricular extra systole/premature ventricular contraction 9.5%, ST elevation 8.7%, sinus tachycardia 6.3%, left atrial enlargement 5.6% , sinus bradycardia 4%, complete RBBB 4%, atrial extra systole/premature atrial contraction 3.2, complete LBBB 2.4%, incomplete LBBB 2.4%, AV block grade 2 type 1 1.6%, microvoltage 1, 6%, RVH 0.8%, and supraventricular tachycardy 0.8%.